Cortes, reconexiones y toma de lectura de medidores de energía eléctrica para usuarios de tipo residencial por telemando - Caiza Simbaña, Luis Mario (2009)
The work of this thesis is to present all readers interested in a further application of radio frequency communication, this time applied to what concerns the single phase electronic meters. The development of this thesis is making cuts, reconnections and meter reading of electricity for residential users by remote control, the application was held in meters that are installed by the electric Company in this is comprised the socio economic, technical and operational, so that serves as a reference guide for all those professionals who intend to engage in a new application for radio frequency communication in a project of this kind in our city, or for those wishing to improve their quality of life, by incorporating new technologies in the home or in different companies.